Performance of HEC-HMS and ArcSWAT models for assessing climate change impacts on streamflow at Bernam River Basin in Malaysia - Ismail, Habibu; Kamal, Md. Rowshon; Lai, Sai Hin; Abdullah, Ahmad Fikri (Universiti Putra Malaysia Press, 2020)
Hydrological models are reliable tools that have been extensively used for hydrological studies. However, the complexity of some of these models has been a major setback, which affects their performance. This study compared Hydrologic Engineering Corps Hydrologic Modeling System (HEC-HMS) with most widely applied Soil Water Assessment Tool (ArcSWAT) model and used to assess impacts of climate change on streamflow at Bernam Basin, Malaysia for 2010-2039, 2040-2069 and 2070-2099 to the baseline period (1976- 2005) using an ensemble of ten GCMs under three RCP scenarios (RCPs 4.5, 6.0 and 8.5). The models performed satisfactorily. However, HEC-HMS performed better compared to ArcSWAT with 0.74, 0.71, 4.21 and 0.37; and 0.71, 0.69, 5.32 and 0.31 for R2 , NSE, PBIAS and RSR, respectively, during the calibration and validation periods. Future periods suggest a decreasing pattern in streamflow, with a higher percentage (−5.94%) expected for the RCP 8.5 scenario in the late century (2080s) during dry season period. In the wet season, streamflow decreases in all future periods except for RCP4.5 where it is expected to increase (0.36%). Therefore, the Basin may likely experience tremendous pressure in the late century due to low streamflow, particularly in dry season months.